On color fixing groups associated with colored symmetrical tilings - Say-Awen, April Lynne D (Archīum Ateneo, 2015)
In this paper, we contribute to the study of colored symmetrical tilings by giving formulas for their associated color fixing groups. In the second part of the paper we provide an application of the results in describing symmetry groups of nanostructures.